Spectral–temporal biphoton waveform of photon pairs from cascade-type warm atoms - Park, Jiho (Sci Rep, 2020)
We investigate the spectral–temporal biphoton waveforms of the photon pairs emitted from cascade-type two-photon-coherent warm (87)Rb atoms via the spontaneous four-wave mixing process in the 5S(1/2)–5P(3/2)–5D(5/2) transition, under the condition of the different detuning frequencies (symmetric detuning conditions of ± 1 GHz) of the pump and coupling lasers relative to the 5P(3/2) state. In both detuning cases corresponding to ± 1 GHz, the biphoton temporal waveforms and biphoton spectral waveforms of the photon pairs are measured by means of time-resolved coincidence photon counting and stimulated measurements, respectively. Although photon-pairs were generated using opposite detunings, we confirm that the spectral–temporal biphoton waveforms of the photon pairs are very similar. Furthermore, we observe Hong–Ou–Mandel interference with 82% visibility with the two independent heralded single photons.